Le Financement de la recherche universitaire - Thür, Livia M. (Canadian Journal of Higher Education, 1977)
Starting now, we must make better long range plans for our various schemes of financing university research. With the rapid growth of the Canadian economy from 1962 to 1974, we saw the establishment of several programs for financing university research. A trend we saw in other areas as well. This expansionist policy came to a plateau in the early 1970's. The deterioration in economic growth now demands that we revise these generous practices. It is not a question of cutting out these important programs, nor of curtailing plans of any new program. We must however learn how to better co-ordinate these efforts.